Human embryonic stem cells. (February 2016) - Damdimopoulou, Pauliina; Rodin, Sergey; Stenfelt, Sonya; Antonsson, Liselotte; Tryggvason, Karl; Hovatta, Outi
Abstract : The establishment of permanent human embryonic stem cell lines (hESCs) was first reported in 1998. Due to their pluripotent nature and ability to differentiate to all cell types in the body, they have been considered as a cell source for regenerative medicine. Since then, intensive studies have been carried out regarding factors regulating pluripotency and differentiation. hESCs are obtained from supernumerary human IVF (in vitro fertilization) embryos that cannot be used for the couple's infertility treatment. Today, we can establish and expand these cells in animal substance-free conditions, even from single cells biopsied from eight-cell stage embryos. There are satisfactory tests for the demonstration of genetic stability, absence of tumorigenic mutations, functionality, and safety of hESCs. Clinical trials are ongoing for age-related macular degeneration (AMD) and spinal cord injury (SCI). This review focuses on the present state of these techniques. Highlights: Human embryonic stem cell (hESC) can be derived from a single eight-cell embryo blastomere. hESC can be derived, expanded, and maintained in defined, xeno-free conditions. The safety, functionality, and stability of hESC lines can be experimentally studied. hESC-based clinical therapies for several conditions are ongoing.